2009
DOI: 10.1111/j.1743-6109.2008.01157.x
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Microencapsulation of Khat: Effects on Sexual Motivation and Estradiol Level in Female Rats

Abstract: Introduction Khat (Catha edulis) is an evergreen tree/shrub that is thought to affect sexual motivation or libido. Its positive effect on sexual desire is more frequently observed in females than in males and occurs when khat is chewed. Thus, khat’s effects on sexual behavior may depend on the release mode of its active constituent. Aim This study aimed to investigate the effect of dried khat alkaloids on the sexual motivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 76 publications
2
8
0
Order By: Relevance
“…Typically, 100 g of dried leaves yielded 8 g of khat extract powder. As previously described, high performance liquid chromatography analysis confirmed that alkaloids in the khat extract consisted of 80% cathine and 20% norephedrine; no cathinone was detected (Aziz et al, 2009;Banjaw and Schmidt, 2005;Dimba et al, 2004).…”
Section: Extraction Of Dried Khat Leavessupporting
confidence: 75%
See 1 more Smart Citation
“…Typically, 100 g of dried leaves yielded 8 g of khat extract powder. As previously described, high performance liquid chromatography analysis confirmed that alkaloids in the khat extract consisted of 80% cathine and 20% norephedrine; no cathinone was detected (Aziz et al, 2009;Banjaw and Schmidt, 2005;Dimba et al, 2004).…”
Section: Extraction Of Dried Khat Leavessupporting
confidence: 75%
“…Khat was extracted from leaves as described previously (Aziz et al, 2009;Banjaw and Schmidt, 2005;Dimba et al, 2004). Briefly, dried khat leaves (100 g) were chopped into small pieces, homogenized in 100 mL of 95% ethanol, centrifuged at 5000 rpm for 5 min and the supernatant then filtered with Whatman filter paper (no.…”
Section: Extraction Of Dried Khat Leavesmentioning
confidence: 99%
“…Typically, 100 g of dried leaves yielded 8 g of khat extract powder. As previously described, high performance liquid chromatography analysis confirmed that the alkaloids in the khat extract consisted of 80% cathine and 20% norephedrine; no cathinone was detected (14,21,22). Lyophilized khat extract was dissolved in Hank's buffered salt solution (HBSS) without Ca 2+ , Mg 2+ to a final concentration of 200 µg/ml and filter (0.2 µm) sterilized before being added to the cells.…”
Section: Methodsmentioning
confidence: 64%
“…After drying, the plant was weighed, packed in a closed foil packet and stored at 4˚C until use. Khat was extracted from the leaves as described previously (14,21,22). Briefly, dried khat leaves (100 g) were swiftly chopped into small (5 mm) pieces and dissolved in 100 ml of 95% ethanol, centrifuged at 5,000 rpm for 5 min and the supernatant then filtered with Whatman filter paper.…”
Section: Methodsmentioning
confidence: 99%
“…Khat extract enhanced sexual motivation, increased vaginal secretions and up-regulated estradiol level in female rats [48].…”
Section: Khat and Reproductive Systemmentioning
confidence: 91%